TRANSFORMASI KEARIFAN LOKAL DALAM PENGEMBANGAN PARIWISATA KREATIF, STUDI INOVASI PADA DESA ASINAN KABUPATEN SEMARANG - Septivosari Mendrofa; Mistriani, Nina (JURNAL ILMIAH EDUNOMIKA, 2025)
The foundation of creative tourism is local knowledge that can both increase tourist attractions and conserve local culture. There is a lot of local cultural potential in Asinan Village, Semarang Regency, but it is insufficient to create innovative, participatory, and informative tourism goods. The purpose of this study is to investigate how local knowledge may be transformed into innovative tourism practices that offer experiences centered around cultural education. Using a case study methodology and descriptive qualitative methods, this study was carried out through document analysis, interviews, and observation. Finding adaptable aspects of local culture, innovative approaches to producing tourism goods, and the ways in which local communities are involved in the process were the main goals of the study. According to the report, using local cultural customs, particular cuisine, and traditional arts as tourism